Analysis of the Role of Parents in Online Learning in Class V Elementary School Mathematics Subjects in Tangerang City - DW Cahyani, Anggit; Awiria; Perdiansyah M.Pd, Ferry (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
The focus of this study is to determine the role of parents as educators, motivators, role models and as friends for online learning in mathematics. The other purpose of this research is to describe how the role of parents in online learning in mathematics. This research is descriptive qualitative research. In this study using data collection with the method of observation, interviews and documentation by zoom meeting. The results of the research on the role of parents in students' online mathematics learning show that: the role of parents is very influential on students' online mathematics learning activities such as the encouragement that has been given to children is able to make children more enthusiastic in mathematics learning activities and a conducive environment can make children feel comfortable and calm during the lesson. Although there are still some parental roles that are not carried out and are still quite lacking.